Spatial and temporal variations in the plankton community because of water and sediment regulation in the lower reaches of Yellow River. (10th July 2020) - Song, Jie; Hou, Chuanying; Liu, Qi; Wu, Xuefei; Wang, Yuanjian; Yi, Yujun
Abstract: The water and sediment regulation (WSR) regime at the Xiaolangdi Hydropower Station in the Yellow River impacts significantly on the aquatic ecosystems in the middle and lower reaches of the river. In this study, we evaluated the influence of the WSR regime on aquatic ecosystems, using the plankton community as an indicator because of their sensitivity to changes in the environment. The plankton distribution and the environmental conditions in the middle and lower reaches of the Yellow River (a total of 810 km) were investigated in three sampling surveys; namely, before, during, and after WSR at the power station. The results showed that the WSR regime influenced both the phytoplankton and zooplankton. For example, the species succession of phytoplankton, from Bacillariophyta to Cyanophyta, then to Chlorophyta, was accelerated, and zooplankton were transported from the reservoir, leading to a temporary increase in the zooplankton biomass downstream. The WSR influenced the phytoplankton and zooplankton over about 540 and 15 km of the river, respectively. A structural equation model was built for the three stages of WSR from data of the plankton biomass and environmental factors. The results showed that environmental factors such as dissolved oxygen (with a coefficient of 0.86 pre-WSR,  −0.47 at inter-WSR, and 0.82 at post-WSR), temperature (with coefficient of −0.76 at inter-WSR), chlorophyll-a (with coefficient of 0.80 at inter-WSR) and conductivity (with coefficient of −0.82 at post-WSR) were important for the plankton biomass. Under the WSR, the concentrations of nutrients such as dissolved silicate, nitrogen, and phosphorus changed, with impacts on the plankton biomass. Even when the environmental and nutrient conditions were optimal, the WSR regime also weakened the predation of zooplankton on phytoplankton and changed the relationships within the plankton community.